2009
DOI: 10.31729/jnma.216
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Fine Needle Aspiration in Evaluation of Male Infertility

Abstract: Fine needle aspiration cytology of superficial as well as of deep seated lesions is now well recognized in diagnosis of neoplastic as well as nonneoplastic and inflammatory lesions. Recently it has also gained popularity for its diagnostic and therapeutic role in male infertility. The purpose of this article was to review various studies published on role of testicular fine needle testicular cytology in male infertility and provide a brief information on method of testicular fine needle aspiration, interpretat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Therefore, in addition to conventional andrological evaluations involving general clinical examination, reproductive examination and sperm analysis (Schrag and Larson, 2016), complementary techniques such as testicular needle aspiration biopsy (TNA) may provide more accurate information on spermatogenesis (Souza et al, 2004); and is indicated for fertility investigations involving oligozoospermia or azoospermia, also for the differential diagnosis of testicular pathologies (Papa and Leme, 2002). TNA allows the recovery of spermatogenic cells directly from the testis and can be used for several research purposes (Jha and Sayami, 2009;Mallidis and Baker, 1994), without depending on the collection and evaluation of semen as a semiological method for the evaluation of male fertility (Papa and Leme, 2002). The amount of spermatogenic cells obtained from TNA has a positive correlation with open testicular biopsies, demonstrating that testicular fine-needle aspiration is the method of choice for investigation of azoospermia in men (Adhikari, 2009;Jensen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in addition to conventional andrological evaluations involving general clinical examination, reproductive examination and sperm analysis (Schrag and Larson, 2016), complementary techniques such as testicular needle aspiration biopsy (TNA) may provide more accurate information on spermatogenesis (Souza et al, 2004); and is indicated for fertility investigations involving oligozoospermia or azoospermia, also for the differential diagnosis of testicular pathologies (Papa and Leme, 2002). TNA allows the recovery of spermatogenic cells directly from the testis and can be used for several research purposes (Jha and Sayami, 2009;Mallidis and Baker, 1994), without depending on the collection and evaluation of semen as a semiological method for the evaluation of male fertility (Papa and Leme, 2002). The amount of spermatogenic cells obtained from TNA has a positive correlation with open testicular biopsies, demonstrating that testicular fine-needle aspiration is the method of choice for investigation of azoospermia in men (Adhikari, 2009;Jensen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The biopsy procedure using needle aspiration began in studies with human medicine in the 1930s and is currently used to evaluate lesions of the mammary gland (Frankel et al, 2011;Freitas et al, 2006;Kemp et al, 2001) and to monitor spermatogenesis in assisted reproduction programs (Gilman et al, 2018;Jha and Sayami, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Testicular fine needle aspiration (FNA) biopsy has been advocated by several authors as an alternative or adjunct approach to surgical biopsy, to evaluate testicular morphology. [ 5 10 ] Testis FNA cytology in several studies correlated well (84 – 97% agreement) with testis biopsy histology in the evaluation of male infertility. [ 11 13 ] In some studies, FNA was even more sensitive than tissue biopsy in detecting the presence of spermatogenesis.…”
Section: Introductionmentioning
confidence: 92%
“…[510] Testis FNA cytology in several studies correlated well (84 – 97% agreement) with testis biopsy histology in the evaluation of male infertility. [1113] In some studies, FNA was even more sensitive than tissue biopsy in detecting the presence of spermatogenesis.…”
Section: Introductionmentioning
confidence: 95%
“…Spermatogenic cells are usually subdivided into spermatogonia, primary and secondary spermatocytes, spermatids, and spermatozoa 2, 3. Knowledge of the cytologic features seen during normal spermatogenesis is critical for recognizing each of these forms.…”
mentioning
confidence: 99%